Dual‐channel type tunable field‐effect transistors based on vertical bilayer WS2(1 − x)Se2x/SnS2 heterostructures. Issue 4 (16th December 2019) - Zheng, Biyuan; Li, Dong; Zhu, Chenguang; Lan, Jianyue; Sun, Xingxia; Zheng, Weihao; Liu, Huawei; Zhang, Xuehong; Zhu, Xiaoli; Feng, Yexin; Xu, Tao; Sun, Litao; et al.
Abstract: Layered semiconductor heterostructures are essential elements in modern electronic and optoelectronic devices. Dynamically engineering the composition of these heterostructures may enable the flexible design of the properties of heterostructure‐based electronics and optoelectronics as well as their optimization. Here, we report for the first time a two‐step chemical vapor deposition approach for a series of WS2(1 − x ) Se2 x /SnS2 vertical heterostructures with high‐quality and large areas. The steady‐state photoluminescence results exhibit an obvious composition‐related quenching ratio, revealing a strong coherence between the band offset and the charge transfer efficiency at the junction interface. Based on the achieved heterostructures, dual‐channel back‐gate field‐effect transistors were successfully designed and exhibited typical composition‐dependent transport behaviors, and pure n‐type unipolar transistors to ambipolar transistors were realized in such systems. The direct vapor growth of these novel vertical WS2(1 − x ) Se2 x /SnS2 heterostructures could offer an interesting system for probing new physical properties and provide a series of layered heterostructures for high‐quality devices. Abstract : Using a two‐step CVD growth method, a series of vertical WS2(1–x)Se2x/SnS2 heterostructures with tunable composition and adjustable band alignment are obtained. Dual‐channel type tunable field‐effect transistors are further designed and probed, which may find some novel applications in next‐generation electronics and optoelectronics.